2023
DOI: 10.3847/1538-4357/acd764
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Thermal Sunyaev–Zel’dovich Effect in the Circumgalactic Medium of Low-mass Galaxies—A Surprising Pattern in Self-similarity and Baryon Sufficiency

Abstract: We report on the measurement of the thermal Sunyaev–Zel’dovich (tSZ) effect in the circumgalactic medium (CGM) of 641,923 galaxies with M ⋆ = 109.8–11.3 M ⊙ at z < 0.5, pushing the exploration of the tSZ effect to lower-mass galaxies compared to those in previous studies. We cross-correlate the galaxy catalog of the Wide-field Infrared Survey Explorer and SuperCOSMOS with Compton-y maps derived from the combined data of the Atacama Cosmology Telescope an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Recently Kim et al (2022) used the IllustrisTNG, EAGLE and FIRE simulations to infer that the properties of the circumgalactic medium (CGM) and the ICM are highly sensitive to feedback prescriptions, and concluded that SZ measurements of the gas can potentially put constraints on theoretical models. A detection of the SZ effect in the CGM has been recently reported by Das et al (2023). In the current work, we use the cosmological simulation SIMBA (D19) to constrain models of AGN feedback using ALMA compact array observations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Recently Kim et al (2022) used the IllustrisTNG, EAGLE and FIRE simulations to infer that the properties of the circumgalactic medium (CGM) and the ICM are highly sensitive to feedback prescriptions, and concluded that SZ measurements of the gas can potentially put constraints on theoretical models. A detection of the SZ effect in the CGM has been recently reported by Das et al (2023). In the current work, we use the cosmological simulation SIMBA (D19) to constrain models of AGN feedback using ALMA compact array observations.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Absorption studies carried out with the Cosmic Origin Spectrograph on the Hubble Space Telescope have probed the cooler phases (10 4 K < T < 10 6 K) of the CGM (e.g., Tumlinson et al 2011;Xavier Prochaska et al 2011;Putman et al 2012;Werk et al 2014Werk et al , 2016Prochaska et al 2017). Stacking analyses of galaxies using Sunyaev-Zeldovich (SZ) measurements have indicated the presence of hot phases in the CGM (Wu et al 2020;Bregman et al 2022;Moser et al 2022;Das et al 2023). However, X-ray observations are best suited to mapping and exploring the physical characteristics of the hot phases of the CGM.…”
Section: Introductionmentioning
confidence: 99%